(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2025)
This scientific article examines the role of artistic literature as a powerful medium in the spiritual development of the individual. Drawing from classical and contemporary literary texts, the article provides an interdisciplinary analysis of how literature cultivates moral values, strengthens personal identity, and fosters national consciousness. The study utilizes hermeneutic and cultural-historical methodologies to explore how fictional narratives shape ethical reflection and societal behavior.